Propagação vegetativa e seleção de genótipos de Jacaranda mimosifolia D. Don para o enraizamento adventício de miniestacas - Fauerharmel, Mariana (2021)
Jacaranda - Jacaranda mimosifolia D. Don – (Bignoniaceae), popularly known as jacaranda, is a tree species widely used in urban afforestation. As for its propagation, most of the available information deals with seed propagation, and little is known about its vegetative propagation. This work aimed to study the production of jacaranda plantlets by mini-cuttings, and select genotypes for their propagation by this technique. A clonal mini-garden was established for the production of mini-cuttings. For adventitious rooting, the mini-cuttings were treated with hydroalcoholic solution of indolebutyric acid (IBA) in the concentration of 0, 1000 or 2000 mg L-1 and cultivated in a greenhouse. Mini-cuttings were evaluated for survival at 30, 60 and 90 days, and for rooting, calluses, shooting, leaf area, root area, aerial dry matter, root dry matter, total dry matter and aerial/root dry matter at 90 days. The rooted mini-cuttings were treated with different volumes of nutrient solution (0, 25 or 50 mL) and evaluated for survival, height, stem diameter, leaf area, root area, aerial dry mass, root dry mass and dry air/root dry mass ratio after 30 days of cultivation in a shade house and full sun area. Twenty-three genotypes were selected for evaluated adventitious rooting competence during six successive collections during 13 months. The genotypes were established in a clonal mini-garden to produce shoots for preparing the mini-cuttings. In each of the six collections, the mini-cuttings were planted in tubes containing commercial substrate and vermiculite, and evaluated for the percentage of rooting and the number of mini-cuttings produced and rooted at 60 days of cultivation in the greenhouse. The components of variance were estimated based on repeated measures by the method of maximum restricted likelihood (REML) and the prediction of phenotypic and genotypic values by the best non-addicted linear prediction (BLUP). Jacaranda can be established in a clonal mini-garden for the production of shoots necessary for the preparation of mini-cuttings. Mini-cuttings root in a greenhouse and without the need of IBA application. The produced plantlets can be acclimatized in a shade house and hardened in full sun. Jacaranda plantlets can be produced by mini-cutting. Genetic variability was observed for the number of produced and rooted mini-cuttings, with the accuracy of 0.84 and 0.74, respectively for six evaluations. Seven jacaranda genotypes were selected for the number of rooted mini-cuttings, resulting in a selection gain of 53.5%. The results of this work show a high potential for breeding jacaranda for vegetative propagation by mini-cuttings and indicate the possibility of high selection gains. The production process of jacaranda plantlets by mini-cutting is very efficient, it does not require the use of growth regulator and a humid chamber for rooting, and allows the use of excess nutrient solution from the fertigation of the clonal mini-garden during the acclimatization and hardening of the plantlets. The jacaranda has great potential for vegetative propagation, and the selection of genotypes is a promising strategy for improvement and production of plantlets by minicutting.